Simultaneous enantioselective determination of omeprazole, rabeprazole, lansoprazole, and pantoprazole enantiomers in human plasma by chiral liquid chromatography–tandem mass spectrometry - Sun, Lu‐Ning; Zhang, Ye; Yang, Yu‐Qing; Shen, Ye; Ying, Yu‐Wen; Su, Yu‐Wen; Zhang, Xue‐Hui; Liu, Yun; Huang, Xu; Wang, Yong‐Qing (Journal of separation science, 2020)
Proton pump inhibitors, including omeprazole, rabeprazole, lansoprazole, and pantoprazole, achieved simultaneous enantioselective determination in the human plasma by chiral liquid chromatography–tandem mass spectrometry. The four corresponding stable isotope‐labeled proton pump inhibitors were adopted as the internal standards. Each enantiomer and the internal standards were extracted with acetonitrile containing 0.1% ammonia, then separated with a Chiralpak IC column (5 µm, 4.6 mm × 150 mm) within 10 min. The mobile phase was composed of acetonitrile–ammonium acetate (10 mM) containing 0.2% acetic acid (50:50, v/v). To quantify all enantiomers, an API 4000 tandem mass spectrometer was used, and multiple reaction monitoring transitions were performed on m/z 360.1→242.1, 384.1→200.1, 370.1→252.1, and 346.1→198.1, respectively. No significant matrix effect was observed for all analytes. The calibration curve for all enantiomers were linear from 1.25 to 2500 ng/mL. The precisions for intra‐ and inter‐run were < 14.2%, and the accuracy fell in the interval of –5.3 to 8.1%. Stability of samples was confirmed under the storage and processing conditions. The developed method was also suitable for separation and determination of ilaprazole enantiomers. The validated method combining the equilibrium dialysis method was applied to the protein binding ratio studies of four pairs proton pump inhibitor enantiomers in human plasma.